The Role of Trust in Moderating the Influence of Service Quality on the Satisfaction of Umrah Pilgrims of PT Ila Safinatin Najah - Nahendra, Nanang; Herman Halim, Edyanus; Jahrizal, Jahrizal (Indonesian Journal of Economics, Social, and Humanities, 2025)
This study aims to analyze the role of trust in moderating the effect of service quality on the satisfaction of umrah pilgrims of PT Ila Safinatin Najah. This study consists of three variables, namely, service quality (X), trust (Z), and satisfaction (Y). Research questions in this study include the effect of service quality on satisfaction, the effect of trust on satisfaction, and the effect of service quality moderated by trust on the satisfaction of the umrah pilgrims of PT Ila Safinatin Najah. The sample in this study were pilgrims who had left for Umrah with PT Ila Safinatin Najah in Pekanbaru city, totaling 90 respondents. Data collection was carried out by giving questionnaires to respondents, and the data analysis used was multiple linear regression analysis and moderate regression analysis (MRA) with the help of SPSSThe results showed that service quality has a positive and significant effect, trust has no positive and significant effect, and service quality moderated by trust has no positive and significant effect on the satisfaction of Umrah pilgrims at PT Ila Safinatin Najah.